Beneficial Effects of Combining Computed Tomography Enteroclysis/Enterography with Capsule Endoscopy for Screening Tumor Lesions in the Small Intestine - Hiroaki Shibata; Shinichi Hashimoto; Kensaku Shimizu; Ryo Kawasato; Tomohiro Shirasawa; Takayuki Yokota; Hideko Onoda; Takeshi Okamoto; Jun Nishikawa; Naofumi Matsunaga; Isao Sakaida (Gastroenterology Research and Practice)
Aim. To compare the efficacy of using computed tomography enteroclysis/enterography (CTE), capsule endoscopy (CE), and CTE with CE for diagnosing tumor lesions in the small intestine. Materials and Methods. We included 98 patients who underwent CE during the observation period and were subjected to CTE at our hospital from April 2008 to May 2014. Results. CTE had a significantly higher sensitivity than CE (84.6% versus 46.2%, P=0.039), but there were no significant differences in specificity, positive or negative predictive values, or diagnostic accuracy rates. The sensitivity of CTE/CE was 100%, again significantly higher than that of CE P=0.002. The difference in specificity between CTE/CE and CE was not significant, but there were significant differences in positive predictive values (100% for CTE/CE versus 66.7% for CE, P=0.012), negative predictive values (100% versus 92.1%, P=0.008), and diagnostic accuracy rate (100% versus 89.8%, P=0.001). The diagnostic accuracy rate was also significantly higher in CTE/CE versus CTE (100% versus 95.9%, P=0.043). Conclusion. Our findings suggested that a combination of CTE and CE was useful for screening tumor lesions in the small intestine. This trial is registered with number UMIN000016154.